Design and methods of a randomised double-blind trial of adding liraglutide to control HbA1c in patients with type 2 diabetes with impaired glycaemic control treated with multiple daily insulin injections (MDI-Liraglutide trial). Issue 1 (February 2015) - Lind, Marcus; Hirsch, Irl B.; Tuomilehto, Jaakko; Dahlqvist, Sofia; Torffvit, Ole; Pehrsson, Nils-Gunnar
Highlights The first study of its kind on incretin-based therapy together with MDI therapy. The majority of the studied patient group can be found in primary care settings. Glycaemic variability will be evaluated by masked continuous glucose monitoring.